2008
DOI: 10.1016/j.jacc.2007.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Provision of Statin and Aspirin After the Detection of Coronary Artery Calcium Within a Community-Based Screening Cohort

Abstract: In this prospective cohort, the presence of coronary calcification was associated with an independent 3-fold greater likelihood of statin and aspirin usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 22 publications
2
72
1
3
Order By: Relevance
“…The current study lends support to the findings of various studies that have demonstrated a significant association between the effects of CAC screening and statin therapy adherence [12,14,17,18]. Kalia et al [14] examined 505 asymptomatic individuals and determined adherence was lowest (44%) among those in the first quartile of CAC scores (0-30) and highest (91%) among those in the fourth quartile (≥526).…”
Section: Prior Studiessupporting
confidence: 83%
See 2 more Smart Citations
“…The current study lends support to the findings of various studies that have demonstrated a significant association between the effects of CAC screening and statin therapy adherence [12,14,17,18]. Kalia et al [14] examined 505 asymptomatic individuals and determined adherence was lowest (44%) among those in the first quartile of CAC scores (0-30) and highest (91%) among those in the fourth quartile (≥526).…”
Section: Prior Studiessupporting
confidence: 83%
“…However, our study, with over 4 years of follow-up, shows high persistence. In addition, the study by Taylor et al [17] demonstrated increasing compliance over 6 years of follow-up.…”
Section: Study Limitationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Other preventive behavioral measures, such as the regular practice of physical exercises and the adoption of healthier diets, have also shown an improvement in the subgroup with higher CACS values. Moreover, in a prospective study following 1,640 patients up for a mean period of six years, the use rates of statins and aspirin were 3.5 and 3 times greater, respectively, in the subgroup with calcification plaques on the CACS 24 . That significant increase did not depend on other risk factors According to the results of the JUPITER study 25 , a large number of asymptomatic patients with LDL levels considered normal have begun to have indication for statin treatment.…”
Section: Potential To Change Clinical Managementmentioning
confidence: 96%
“…[10][11][12] Wong and colleagues 11 showed in 703 asymptomatic patients that underwent CAC score, that the presence of CAC was an independent predictor of risk reducing behaviors such as increased use of aspirin and cholesterol lowering medications as well as consultation with a physician. In a separate study, Taylor et al 10 attempted to answer the question of whether a screening calcium score results in changes in subsequent aspirin and statin. Among 1640 active duty male army personnel, they showed that the presence of coronary calcification (CAC [ 0) was associated with an independent 3-fold greater likelihood of statin and aspirin usage.…”
mentioning
confidence: 99%